IDENTIFIKASI TINGKAT KECURANGAN AKADEMIK DI LINGKUNGAN PERGURUAN TINGGI (Studi Pada Fakultas Ekonomi dan Bisnis Universitas Bengkulu) - Halimatusyadiah Halimatusyadiah; Aditiyawarman Nugraha (UNIB Press, 2017)
This study aims to identify the academic fraud that occur in the environment college. Academic fraud was identified in this study is a fraud committed by students, faculty and employees. The population in this study were students of the Faculty of Economics and Business, University of Bengkulu class of 2011 - 2012. Based on the method Slovin, gained 88 people who serve as research samples. This study uses two methods of data collection, the questionnaire method and interview method. This study found that the highest fraud that has occurred is cheating